Circuito de acionamento de chaves semicondutoras de potência empregando transformador piezoelétrico - Fabero, Fabrício Girardon (2020)
This thesis presents a proposal for a gate-driver system, for MOSFET and IGBT power semiconductor devices, which uses a piezoelectric transformer in the power circuit and communication channel. Thus, a bibliographical review of the already known topologies of gate-drivers communication channel and energy transmission was conducted, focusing on isolated structures, where the potentiality of using piezoelectric transformers in this type of application was identified. Therefore, for simplicity, an E-Class converter was used to power the transformer, implementing both the isolated source and the communication channel of the gate-driver circuit. So, the study of the Class-E converter was conducted, involving the modeling of the converter together with a screening of the resonance frequency and the piezoelectric transformer's ratios. A detailed analysis of the piezoelectric transformer was also made to obtain its equivalent electrical model to identify the resonance frequencies and, consequently, its point of operation. Also, regarding the E-Class converter, modulation and demodulation techniques for the gate-driver circuit command signal are proposed. Finally, experimental results for a gate-driver circuit with 30 V supply voltage and command signal between -5 and +15 V are presented for the validation of the proposal.